2019
DOI: 10.1002/jlb.4a0319-079rr
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure to hypoxia induces an autophagy-like cell survival program in human neutrophils

Abstract: Neutrophils contribute to low oxygen availability at inflammatory sites through the generation of reactive oxidants. They are also functionally affected by hypoxia, which delays neutrophil apoptosis. However, the eventual fate of neutrophils in hypoxic conditions is unknown and this is important for their effective clearance and the resolution of inflammation. We have monitored the survival and function of normal human neutrophils exposed to hypoxia over a 48 h period. Apoptosis was delayed, and the cells rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…However, there may also be untoward consequences from the large influx of neutrophils into a hypoxic environment. Hypoxia has been shown to inhibit spontaneous neutrophil apoptosis (Talla et al, 2019) and is also thought to induce degradation of azurophilic granules with the potential for exacerbation of tissue injury from spillage of granule proteins at hypoxic injury sites. While extended neutrophil survival could be beneficial for pathogen clearance, it is unclear what effects their continuing accumulation could have on an already damaged tissue environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there may also be untoward consequences from the large influx of neutrophils into a hypoxic environment. Hypoxia has been shown to inhibit spontaneous neutrophil apoptosis (Talla et al, 2019) and is also thought to induce degradation of azurophilic granules with the potential for exacerbation of tissue injury from spillage of granule proteins at hypoxic injury sites. While extended neutrophil survival could be beneficial for pathogen clearance, it is unclear what effects their continuing accumulation could have on an already damaged tissue environment.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, the process by which damaged intracellular components are cleared by a homeostatic degradation pathway, promotes neutrophil degranulation-autophagy-deficient murine neutrophils exhibited reduced secretion of all three major granule subtypes (assessing MPO, lactoferrin, and MMP-9 release) [88]. Hypoxia has been shown to increase expression of LC3B-II, a protein indicative of autophagosome formation, in neutrophils, [89] and, hence, hypoxia-driven autophagy may contribute to increased degranulation. Furthermore, pan-PI3K inhibition reduced the formation of autophagosomes in hypoxic but not normoxic neutrophils, although this effect was only seen at 5 h (81).…”
Section: Roles Of Autophagy and Reactive Oxygen Species In Neutrophilmentioning
confidence: 99%
“…Both phagocytosis-dependent and -independent induction of autophagy have been shown, with uniform upregulation of LC3B and both processes reduced by PI3K inhibition; however, the reliance of phagocytosis-independent autophagy on ROS is less strict [94]. Of note, the aforementioned studies addressing neutrophil degranulation or hypoxia in association with autophagy demonstrated no differences in phagocytic capacity [88,89]. Overall, autophagy, which appears to increase degranulation, can be enhanced by both hypoxia and PI3K signalling, but the balance of interaction between autophagy and ROS in hypoxic situations, and the potential effect this has on degranulation, is complex and requires further clarification.…”
Section: Roles Of Autophagy and Reactive Oxygen Species In Neutrophilmentioning
confidence: 99%
“…Or inhibition of margination [10] or hypoxia. Hypoxia inhibits neutrophil apoptosis and subsequently increases neutrophil numbers [11]. In this work, 61.7%, 58.2%, 59.3%,25%,52.9% of leukocytosis, neutrophilia, monocytosis, eosinophilia, and basophilia were present in the critical cases at presentation.…”
Section: Discussionmentioning
confidence: 46%